Effects of Biochar Amendment on CO2 Evolution in Four Ecotypes of Leyte Sab-A Basin Peatland, Philippines: 10.32526/ennrj/23/20240274 - Bobon-Carnice, Pearl Aphrodite; Socias, Grechelle N.; Corcilles, Mary Yolle S.; Abaño, Trisha Keith B.; Espanta, Uzzel Maureen H. (Environment and Natural Resources Journal, 2025)
Atmospheric carbon cycle criticisms are significant liabilities in existing predictions of future climate. Carbon dioxide (CO2) discharges caused by climate warming through dense peat stores will frame a stable positive carbon cycle–atmospheric input. An experimental-descriptive analytical method was used to acquire data on quantifying the amount of CO2 evolved in the four adjacent ecotypes of Leyte Sab-A Basin Peatland (LSBP), Philippines, both with and without biochar incorporation. Results showed that after 120 days of incubation, the CO2 evolved between ecotypes measured 0.73 mg CO2/g, 0.31 mg CO2/g, 0.23 mg CO2/g, and 0.20 mg CO2/g for TML (marshland), TPF (peat forest), TAL (agricultural land), and TMV (mixed vegetation), respectively. In comparison, treatments with biochar were 0.81 mg CO2/g, 0.57 mg CO2/g, 0.46 mg CO2/g, and 0.43 mg CO2/g for TMLB (marshland+biochar), TPFB, TMVB, and TALB, respectively. Results rendered significant differences between ecotypes, and between those with added biochar (p-value: 1.8E-06). This study concludes that TML with and without biochar had the highest evolved CO2 over time, implying the best ecosystem preservation among the ecotypes. For future studies, these findings establish a scientific basis for adaptive response assessment of peatlands to climate change, and for decisions made in support of policy changes.